Relationship of religious motivation with some demographic variables among Taiwanese female novices - Lee, Fatima Su-Chen (Animo Repository, 1992)
This study investigates the relationship of religious motivation with given demographic variables namely age, educational attainment, and religion (number of years since baptism and parents' religion) among Taiwanese female novices and to present a descriptive profile of the novices' level of religious motivation. Thirty-two (32) Taiwanese female novices who attended the Joint Taiwan Female Novices Formation Program were the subjects of this study. The Menguito Religious Motivation Questionnaire (RMQ) which was used to assess the level of religious motivation, had three component factors: Factor 1, the motive of service in working for social justice. Factor II, the motive of achieving Christian perfection and the motive of sacrificial worship in response to an inner calling. Factor norms were developed by the researcher from Menguito's data to be able to analyze the current data meaningfully. For statistical treatment, means, percentile scores, Pearson product Moment, t-test and One-Way ANOVA were employed. The findings of this study were: 1. In general, the Taiwanese female novices under study had inadequate motivation for service especially in working for social justice (Factor I). 2. There is a significant relationship between religious motivation Factor II, (the motive of achieving Christian perfection) and educational attainment, at .01 level. 3. No significant relationship was found between the religious motivation factors and the other demographic variables under study. One recommendation given by the researcher is that an enrichment guidance program for intensifying the motivation of service especially in working for social justice, could be integrated into the novitiate plan.